2015
DOI: 10.1021/ja511572q
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Hybrid Catalyst of Cobalt-Doped FeS2 Nanosheets–Carbon Nanotubes for Hydrogen Evolution Reaction

Abstract: Hydrogen evolution reaction (HER) from water through electrocatalysis using cost-effective materials to replace precious Pt catalysts holds great promise for clean energy technologies. In this work we developed a highly active and stable catalyst containing Co doped earth abundant iron pyrite FeS(2) nanosheets hybridized with carbon nanotubes (Fe(1-x)CoxS(2)/CNT hybrid catalysts) for HER in acidic solutions. The pyrite phase of Fe(1-x)CoxS(2)/CNT was characterized by powder X-ray diffraction and absorption spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
413
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(428 citation statements)
references
References 49 publications
10
413
1
2
Order By: Relevance
“…S7 in the ESM), further indicating a faster electron transfer [34][35][36]. The outstanding HER activity of the ternary NiCoP NSA electrode can be attributed to the incorporation of metal atoms into binary metal phosphides, which may modify their electronic structure as well as tune the hydrogen adsorption energy [24], leading to the improvement of intrinsic electrocatalytic performance and electron transport.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…S7 in the ESM), further indicating a faster electron transfer [34][35][36]. The outstanding HER activity of the ternary NiCoP NSA electrode can be attributed to the incorporation of metal atoms into binary metal phosphides, which may modify their electronic structure as well as tune the hydrogen adsorption energy [24], leading to the improvement of intrinsic electrocatalytic performance and electron transport.…”
Section: Resultsmentioning
confidence: 98%
“…While significant progress has been made in the study of binary transition metal phosphides as bifunctional catalysts [12,22,23], the application of ternary metal phosphides in hydrogen or oxygen evolution reactions has been scarcely reported, to the best of our knowledge. In addition, previous spectroscopic and theoretical studies demonstrated that the incorporation of additional metal atoms into HER and OER catalysts is crucial for enhancing their electrocatalytic activity by tuning of the electronic structure [24][25][26][27]. Considering the excellent catalytic potential of phosphide-based materials with electronic structure tunable by atom doping, ternary metal phosphides should be superior bifunctional catalysts for overall water splitting, compared with their binary counterparts.…”
mentioning
confidence: 99%
“…For instance, CoP nanocrystals decorated on CNTs were synthesized by the low‐temperature phosphidation of a Co 3 O 4 /CNT precursor 61. Co‐doped iron pyrite nanosheets were interfaced with CNTs (Fe 1–x Co x S 2 /CNT hybrid) by solution reaction of Fe salt, Co salt and thioacetamide, followed by thermal treatment 62. A strong dependence of the Co doping ratio on the HER activity of the Fe 1–x Co x S 2 /CNT hybrid catalyst was found.…”
Section: Hermentioning
confidence: 99%
“…Among them, the low-cost, earthabundant iron sulde has attracted much attention as an electrocatalytic material due to its excellent catalytic activity. 7,18 However, the catalytic performance of iron sulde is limited by its low surface area and lack of active sites. 19 If the non-noble metals electrocatalysts are grown on carbon material substrates, doping with homologous elements not only reduces the catalytic resistance but also exposes more active sites.…”
Section: Introductionmentioning
confidence: 99%